-9(2b+4)+(19b-9)=0

Simple and best practice solution for -9(2b+4)+(19b-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(2b+4)+(19b-9)=0 equation:


Simplifying
-9(2b + 4) + (19b + -9) = 0

Reorder the terms:
-9(4 + 2b) + (19b + -9) = 0
(4 * -9 + 2b * -9) + (19b + -9) = 0
(-36 + -18b) + (19b + -9) = 0

Reorder the terms:
-36 + -18b + (-9 + 19b) = 0

Remove parenthesis around (-9 + 19b)
-36 + -18b + -9 + 19b = 0

Reorder the terms:
-36 + -9 + -18b + 19b = 0

Combine like terms: -36 + -9 = -45
-45 + -18b + 19b = 0

Combine like terms: -18b + 19b = 1b
-45 + 1b = 0

Solving
-45 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 1b = 0 + 45

Combine like terms: -45 + 45 = 0
0 + 1b = 0 + 45
1b = 0 + 45

Combine like terms: 0 + 45 = 45
1b = 45

Divide each side by '1'.
b = 45

Simplifying
b = 45

See similar equations:

| 2x+450000=550000000 | | (6-6x-6x)+3(6x+7)=15 | | 2t+5=5t-4 | | 3+18z-2=7z+29-3z | | 1/6+1/4 | | 3v-5=7v+11 | | 3y^2+28y-20= | | 2x+2(1)=14 | | 23=-2(4+3m)+7 | | 8(x-2)=3(x+5)-2(2x+2) | | 15=-2(2n-1) | | 29=3y+2 | | 8z+10z=72 | | 90xy+108x^2= | | 9b^2-2796+1980=0 | | 5(2+4h)=85 | | 13-x+7x=15 | | x/8=-30 | | 3a+9b+7c=5 | | 3(7+-1y)+2y=20 | | y/6=-10 | | x+.335x=200 | | 5x-y=1/4 | | (-1/6)(x-12)+(1/2)(x+2)=x+27 | | 15+(-b4)=29 | | x^24-y^16= | | 34=-2y+4y+12 | | -(6y+1)-(-5y-7)=5 | | 12x-166=5x-12 | | 4x+5x-12=42 | | 0=2x^2+12x-378 | | 7x+2-x=2 |

Equations solver categories